It’s not only the sea: a history of human intervention in the beach-dune ecosystem of Costa da Caparica (Portugal) - Palma, Monique (2021)
Costa da Caparica, located south of Lisbon, has been since the 1960s the favourite beach of the population of the Portuguese capital. The bridge over the Tagus river (1966), connecting the two margins, has facilitated the access to that wide beach of sand and dunes. Due to its natural features and proximity to Lisbon, Caparica become a highly populated area, where different social and economic activities compete for the use of the available space, increasing pressure upon the local ecosystems. The situation is even more problematic, because that littoral has been deeply affected by coastal erosion from the 1950s onwards. Authorities have been dealing with the issue using groynes and artificial beach nourishments. Since 2015, the Municipality of Almada is investing in the rehabilitation of the dunes of the beach of S. João, placing fences to retain the sand and planting vegetation. This programme is particularly interesting from a coastal management history point of view, because these dunes have been the object of many interventions with different purposes, but what was done and why is not very well known. The aim of this article is therefore to present the results of a historical research about human intervention in Costa da Caparica and, particularly at S. João beach, starting in the 19th century, with the first dunes’ survey, the afforestation experiences and the construction of a drainage system. This paper offers a long-term perspective on the socio-evolution of these hybrid environments. Results and discussion show how dunes were trimmed by the works carried out and the reasons that laid beneath these. Revealing the ideas and values, the social, economic and political pressures, that across the years and within the same time period, shaped management strategies and landscapes.